Biotic soil legacy effects on the seedling performance of early and late successional tree species - Binny, Delia Anne (Nanyang Technological University, 2023)
Soil biotic legacies have long-term effects on the growth and development of plants, could facilitate or inhibit the growth of succeeding plants. Based on this understanding, healthy forest soil is likely to possess greater microbial diversity, which could be utilised to ‘biofertilise’ degraded forests to improve soil functioning and, consequently, plant growth performance – speeding up the rate of forest succession/restoration. However, the extent to which soil biotic legacies from contrasting forest types can enhance growth of early and late successional tree species remains limited. To fill this research gap, I grew seedlings of 6 tree species (3 early and 3 late successional species) in 4 soil inoculum types (primary low-land forest, late native-dominated secondary forest, early secondary forest, and sterilised early secondary forest as a control) in a greenhouse for six months and measured plant biomass gain. Soil nutrient concentrations were measured and found to be similar across inoculum types except for inorganic nitrogen. Additionally, I measured the fungal and bacterial communities of the various unsterilised soil inocula. Soil microbial communities differed in structure, composition and α-diversity among the contrasting forest types. However, these contrasting microbial communities had similar effects on the growth performance of most early and late successional plant species, with the exception of Hopea mengarawan. Therefore, soil biotic legacies and biofertilisation likely have minimal influence in restoration outcomes.